Density of tobacco retail outlets near schools and smoking behaviour among secondary school students - Maree Scully; Molly McCarthy; Meghan Zacher; Charles Warne; Melanie Wakefield; Victoria White (Elsevier, 2013)
Abstract Objective: To investigate whether the density of tobacco retail outlets near schools in Victoria, Australia, is associated with adolescent smoking behaviour. Methods: Cross‐sectional survey data of 2,044 secondary school students aged 12-17 years was combined with tobacco outlet audit data. Associations between students' self‐reported tobacco use and the density of tobacco outlets near schools was examined using multilevel logistic and negative binomial regression models, with cigarette price at local milk bars and key socio‐demographic and school‐related variables included as covariates. Results: Increased tobacco retail outlet density was associated with a significant increase in the number of cigarettes smoked in the previous seven days among students who smoked in the past month (IRR=1.13; 95% CI 1.02-1.26), but not the odds of smoking in the past month in the larger sample (OR=1.06; 95% CI 0.90-1.24), after controlling for local mean price of cigarettes and socio‐demographic and school‐related variables. Conclusions and implications: This study suggests there is a positive association between tobacco retail outlet density and cigarette consumption among adolescent smokers, but not smoking prevalence, in the Australian context. There is value in considering policy measures that restrict the supply of tobacco retail outlets in school neighbourhoods as a means of reducing youth cigarette consumption.